1996
DOI: 10.1161/01.atv.16.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated Fatty Acid–Enriched Diet Decreases Plasma Plasminogen Activator Inhibitor Type 1

Abstract: An increase in levels of plasma plasminogen activator inhibitor type 1 (PAI-1) is one of the main hemostatic alterations in patients with coronary heart disease. Despite growing interest in the fibrinolytic system, few studies have been undertaken to determine the effect exerted on it by the different dietary fatty acids. We investigated the effect of a monounsaturated fat (MUFA)-rich diet in comparison with a low-fat diet (National Cholesterol Education Program step 1 diet) (NCEP-1) on factors involved in blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 52 publications
4
45
0
1
Order By: Relevance
“…However, it should be noted in this context that there are also some clinical studies showing an association between n-3 fatty acid intake and decreased plasma PAI-1 activity. Lopez-Segura et al 43 showed that consumption of a diet rich in monounsaturated fatty acids resulted in a significant decrease in both plasma PAI-1 activity and antigen in healthy individuals. Furthermore, the triglyceride levels were not affected by the dietary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted in this context that there are also some clinical studies showing an association between n-3 fatty acid intake and decreased plasma PAI-1 activity. Lopez-Segura et al 43 showed that consumption of a diet rich in monounsaturated fatty acids resulted in a significant decrease in both plasma PAI-1 activity and antigen in healthy individuals. Furthermore, the triglyceride levels were not affected by the dietary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance and its associated dyslipidemia (high triglyceride, low HDL) have been shown to be more marked on a high-carbohydrate diet compared with a diet rich in monounsaturated fatty acids (38,39,(70)(71)(72)(73)(74)(75)(76)(77). In individuals with diabetes, glycemic control may also be adversely influenced and plasminogen activator inhibitor type 1 levels are increased, suggesting an increased thrombogenic tendency (77).…”
Section: Carbohydrate Fiber and Glycemic Indexmentioning
confidence: 99%
“…In individuals with diabetes, glycemic control may also be adversely influenced and plasminogen activator inhibitor type 1 levels are increased, suggesting an increased thrombogenic tendency (77). However, studies that have examined this issue have generally failed to consider the importance of the nature of the carbohydrate.…”
Section: Carbohydrate Fiber and Glycemic Indexmentioning
confidence: 99%
“…However, controversy now exists between the advisability of following a diet containing 455% carbohydrates and 30% lipids (eg NCEP step 1) with respect to a Mediterranean diet poorer in carbohydrates but richer in lipids and monounsaturated fatty acids (MUFA). Thus, several studies do not confirm the benefits of the former diet over that of the Mediterranean diet with regard to serum triglycerides, HDL-cholesterol and fibrinolysis (Grundy, 1997;Ló pez Segura et al, 1996).…”
Section: Diet Assessmentmentioning
confidence: 99%